2018
DOI: 10.29245/2578-3009/2018/3.1144
|View full text |Cite
|
Sign up to set email alerts
|

T Cells in Atherosclerosis in Ldlr-/- and Apoe-/- Mice

Abstract: Atherosclerosis is the underlying basis for most cardiovascular diseases. It is a chronic inflammation affecting the arterial intima and is promoted by hypercholesterolemia. Cells of both the innate and adaptive immune systems contribute to this inflammation with macrophages and T cells being the most abundant immune cells in the atherosclerotic plaques. In this review, we discuss the studies that examined the role of T cells and T cell subsets in Apoe−/− and Ldlr−/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Besides monocytes-derived macrophages, immune cells, including dendritic cells, mast cells, T cells and B cells, also infiltrate the intima and adventitia of the atherosclerotic plaque [ 66 , 67 ].…”
Section: Pathophysiology Of Atherosclerosismentioning
confidence: 99%
“…Besides monocytes-derived macrophages, immune cells, including dendritic cells, mast cells, T cells and B cells, also infiltrate the intima and adventitia of the atherosclerotic plaque [ 66 , 67 ].…”
Section: Pathophysiology Of Atherosclerosismentioning
confidence: 99%
“…66,67 Studies of the APOA1 and APOE knockout mouse models have demonstrated that these apolipoproteins play a fundamental role in CD4+ T-cell homeostasis and function. 68,69 APOA1-deficient mice displayed decreased levels of HDL and higher risk to develop atherosclerosis. 70 This mouse model is also characterized by a higher frequency of T cells in circulation, as systemic lack of APOA1 primes bone marrow stem cells for T-cell generation.…”
Section: Hdls and Their Interactions With Cd4+ T Cellsmentioning
confidence: 99%
“…Within the plaque, T cells exhibit heterogeneity of functions. Some subsets are pro-inflammatory (T helper cells 1), while others tend to suppress inflammation (T helper cells 2) [ 57 ].…”
Section: Pathogenesis Of Atherosclerosismentioning
confidence: 99%